Perspektif Yesus tentang Hukum Musa (Eksegesis Yohanes 7:53-8:11) dan Implementasinya Bagi Orang Percaya - Mende Maharani Berutu (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
This study aims to find Jesus' perspective on the Law of Moses and apply Jesus' teachings contained in John 7:53-8:11 in the lives of believers. The scribes and Pharisees wanted to test Jesus by bringing a woman caught in adultery. They asked Jesus about the Law of Moses which regulates the punishment for adultery to blame Him. The method used in this study is a qualitative method with a library research approach. In this study, a Biblical study was conducted, especially the New Testament using exegetical steps. The results of the study show that Jesus did not reject the implementation of the Law of Moses. The death penalty was not carried out for the woman because of the wrong motivation of the scribes and Pharisees. They wanted to test Jesus by using the adulterous woman as a tool. Jesus fulfilled the Law of Moses by implementing love as the main thing in carrying out the punishment. Although the death penalty is no longer enforced, believers must be able to apply love in punishing people who commit adultery. Believers must emulate Jesus' attitude of forgiving with love and giving an opportunity to repent. Believers must also not tempt God, not exploit others for personal gain, and must introspect in every action.